2020
DOI: 10.26444/monz/130510
|View full text |Cite
|
Sign up to set email alerts
|

The level of physical activity of university students in Lublin, Bialystok and Covilhã

Abstract: Objectives. The aim of the study is to determine the level and to compare the physical activity of students of the Medical University (MU) in Lublin and the University of Technology (BUT) in Bialystok, Poland, and the University of Beira Interior (UBI) in Covilhã, Portugal. Materials and method. A group of 823 people were examined: 108 students of the Medical University of Lublin, 118 students of Bialystok University of Technology, and 597 students of the University of Beira Interior in Covilhã. The study exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Some studies have found that, before lockdown, Polish students in pro-health fields of study (e.g., physiotherapy, physical education, tourism and recreation) declared high levels of PA (2000–10,000 MET/week). The abovementioned studies were conducted with the IPAQ short-version scale, which means that the results are comparable with ours [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 84%
“…Some studies have found that, before lockdown, Polish students in pro-health fields of study (e.g., physiotherapy, physical education, tourism and recreation) declared high levels of PA (2000–10,000 MET/week). The abovementioned studies were conducted with the IPAQ short-version scale, which means that the results are comparable with ours [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 84%
“…Another study found that half of the university students participating in the study were less active/inactive [ 31 ]. On the other hand, the data obtained from these studies indicate that especially males are more active or, similar to our study, although the level of physical activity is higher in males, it is not statistically significant [ 32 , 33 ]. The prevalence of low physical activity among the students participating in our study may be the effect of an ongoing sedentary period due to the pandemic.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, there was no statistically significant relationship between the department of education and IPAQ scores. In one of the studies examining the physical activity status of different undergraduate departments, it was stated that the frequency of adequate physical activity was higher among medical students [ 33 ]. In our study, IPAQ scores do not differ according to BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The above could be attributed to their academic profile and obligatory participation in various types of PA. According to some studies, Polish students enrolled in health-related university programs (such as physiotherapy, physical education, tourism and recreation) had declared high levels of PA (2000–10,000 METs-min/week) before the lockdown [ 46 , 47 ]. However, the results of our study indicate that the COVID-19 pandemic had a negative impact on the surveyed students’ PA levels.…”
Section: Discussionmentioning
confidence: 99%